Macronutrient deficiency symptoms in lettuce - FILHO, Arthur Bernardes CECÍLIO [UNESP]; RODRIGUES, Marilsa Aparecida [UNESP]; Da SILVA, Maria Letícia Pacheco [UNESP]; CORTEZ, Juan Waldir Mendoza (UNESP - Universidade Estadual Paulista, 2020)
Diagnosis of nutritional problems through observation of symptoms has great practical importance because it allows making quick decisions in the field for correction of deficiencies. This study aimed to describe and photograph the effects of macronutrient omission in lettuce cultivars. The experiment was conducted in hydroponic, at UNESP, Campus of Jaboticabal in São Paulo State. Treatments were applied to cultivars Oak Leaf Red Pixie (crisp group without head, reddish leaves), Lucy Brown (American group, smooth, green leaves) and Veronica (crisp group without head, green leaves). Treatments with the omission of Ca and P in nutrient solution were applied on the same day that the lettuce seedlings were transplanted from nursery to the channels of final growth. After four days, it was applied the solutions with the omission of N, K and Mg. Symptoms of deficiency occur in the following order: N, K, Mg, P and Ca. The nutritional deficiency symptoms were easily observed in 'Veronica' and 'Lucy Brown' and hardly identified in the 'Red Oak Leaf Pixie' due to reddish color of leaves. The omission of nutrients compromises the commercial aspect of the lettuce and the omissions of N, K, Ca and Mg this compromise occurs already in the initial phase of the symptoms.
Sintomas de deficiência de macronutrientes em alface
Keywords: Lactuca sativa; Mineral nutrition; Nutritional deficiency